ANALYSIS OF LOCAL GOVERNMENT POLICY MODELS IN PREVENTING CORRUPTION IN THE VILLAGE GOVERNMENT SECTOR - Achmad Hariri; Samsul Arifin (STIH Putri Maharaja, 2023)
A research problem is related to the number of corruption crimes that occur in a village government sector, especially with the issuance of Law number 6 of 2014 concerning villages (Village Law), in the mandate of the law village governments with the principles of recognition and subsidiarity are given the authority to manage village funds allocation. From the broad authority owned by the village, it has the potential to be misappropriated due to many factors that includes human resources factors of the village apparatus, political factors and also the existence of power relations. The research purpose determined the regional government policy model in an effort to prevent corruption in the village government sector which was a model for local government policies. Therefore, the corruption in the village is increasingly suppressed. While this research method used empirical juridical research methods, the empirical approach sees law as a social, cultural reality or das sein. Since the primary data used were obtained directly from Bangkalan in this research. The result showed that the local governments had the obligation to supervise village governments as article 115 of Law Number 6 of 2014 concerning the villages. It stated that districts / cities have a vital role, namely supervising village governments. Moreover, the minister of home affairs regulation number 113 of 2014 concerning village financial management explained that the government provinces are required to foster and supervise the provision and distribution of village funds, allocation of village funds, and revenue sharing of local taxes and levies from districts/cities. The potential for misappropriation of village government governance is caused by many factors, including human resources of village apparatus, political factors and also the existence of power relations. The policy model of the Bangkalan Regency Regional Government in an effort to reduce the misappropriation of power, especially the criminal act of corruption committed by thevillage apparatus, is still minimal.